2021
DOI: 10.1080/15592324.2021.2005882
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of beneficial orchid mycorrhizal fungi in Paphiopedilum barbigerum (Orchidaceae)

Abstract: Seed germination and seedling development in nearly all orchid species rely on a symbiotic relationship with mycorrhizal fungi; however, this is not the case with all mycorrhizal fungi. This study aims to provide an understanding about the important role of mycorrhiza in seed germination and growth of Paphiopedilum barbigerum . Therefore, we isolated and identified endophytic fungi from the roots of wild P. barbigerum . The beneficial mycorrhizal fungi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 49 publications
(36 reference statements)
2
18
0
Order By: Relevance
“…Epulorhiza sp. FQXY019 had been isolated from the mycorrhizal roots of P. barbigerum in our previous study ( Tian et al, 2022 ). First, a layer of cellophane was placed onto 9 cm Petri dishes containing 30 mL potato dextrose agar (PDA) medium (200 g potato, 10 g agar, 20 g glucose, and 1 L distilled water).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Epulorhiza sp. FQXY019 had been isolated from the mycorrhizal roots of P. barbigerum in our previous study ( Tian et al, 2022 ). First, a layer of cellophane was placed onto 9 cm Petri dishes containing 30 mL potato dextrose agar (PDA) medium (200 g potato, 10 g agar, 20 g glucose, and 1 L distilled water).…”
Section: Methodsmentioning
confidence: 99%
“…Herein, we investigated the germination of P. barbigerum, a rare Paphiopedilum native to southwest China with high ornamental value, in the presence of a mycorrhizal fungus, Epulorhiza sp. FQXY019, which we had previously isolated and which progressed seed germination of P. barbigerum ( Tian et al, 2022 ). Based on this, we integrated transcriptomics analyses with proteomic techniques to investigate the genes and proteins differentially expressed in the seed germination of P. barbigerum with and without Epulorhiza sp.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, their inoculation is suitable during plant cultivation, especially during the propagation of the species toward reintroduction (Cribb et al 2003;Nogueira et al 2005;Li et al 2021b). Once an orchid is reintroduced in nature with endophytes, both the plant and its symbionts are preserved and reintroduced, which increases the chances of occurrence of natural propagation and the maintenance of the orchid life cycle (Cribb et al 2003 Implementing symbiotic propagation requires culture-dependent studies, where endophytic fungi are isolated, classi ed, and then, used in a co-inoculation test to select appropriate isolates for orchid propagation Valadares 2012, 2017;Tian et al 2021). Although fungal isolation has been an important source of information about orchid mycorrhizal root endophytes (Pereira and Valadares 2017;Li et al 2021a), culture-independent studies are performed using next-generation sequence (NGS) platforms, which improve knowledge about root fungal community (Waud et al 2016;Li et al 2021a), provide broad information about the most important fungal endophytes on orchid roots and so as give support during the selection of appropriate fungal isolates to be applied in further orchid propagation programs.…”
Section: Introductionmentioning
confidence: 99%
“…The endophytes in orchids are mostly specific fungi of Basidiomycota, such as Sebacinaceae, Ceratobasidiaceae, and Tulasnellaceae ( Zettler and Corey 2018 ; Li et al 2021 ; Wang et al 2021 ). In addition, some endophytes from the root, especially Fusarium (Ascomycota), are thought to form mycorrhizae with orchids ( Tian et al 2022 ). Chen et al (2010) found that Fusarium is the dominant endophytic fungi in the medicinal orchid Dendrobium loddigesii and could improve its growth rate and biomass.…”
Section: Introductionmentioning
confidence: 99%